Differential Biological Effects of Dietary Lipids and Irradiation on the Aorta, Aortic Valve, and the Mitral Valve - Donis, Nathalie; Jiang, Zheshen; D'Emal, Céline; Hulin, Alexia; Debuisson, Margaux; Dulgheru, Raluca; Nguyen, Mai-Linh; Postolache, Adriana; Lallemand, François; Coucke, Philippe; Martinive, Philippe; Herzog, Marielle; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Dietary cholesterol and palmitic acid are risk factors for cardiovascular diseases (CVD) affecting arteries and heart valves. Ionizing radiation that is frequently used as anticancer treatment promotes CVD. The specific pathophysiology of these distinct disease manifestations is poorly understood. We therefore studied biological effects of these dietary lipids and cardiac irradiation on arteries and heart valves in rabbit models of CVD. Methods and results: Cholesterol-enriched diet led to thickening of aortic wall and aortic valve leaflets, immune cell infiltration in aorta, mitral and aortic valves, as well as aortic and aortic valve calcification. Numerous cells expressing -smooth muscle actin were detected in both mitral and aortic valves. Lard-enriched diet induced massive aorta and aortic valve calcification, with no detectable immune cell infiltration. The addition of cardiac irradiation to cholesterol diet yielded more calcification and more immune cell infiltrates in atheroma and aortic valve than cholesterol alone. RNAseq analyses of aorta and heart valves revealed that cholesterol-enriched diet mainly triggered inflammation-related biological processes in aorta, aortic and mitral valves, which was further enhanced by cardiac irradiation. Lard-enriched diet rather affected calcification- and muscle-related processes in aorta and aortic valve, respectively. Neutrophil count and systemic levels of platelet factor 4 and ent-8-iso-15(S)-PGF2α were identified as early biomarkers of cholesterol-induced tissue alterations, while cardiac irradiation resulted in elevated levels of circulating nucleosomes. Conclusion: Dietary cholesterol, palmitic acid and cardiac irradiation combined with cholesterol-rich diet led to the development of distinct vascular and valvular lesions, and changes in circulating biomarkers. Hence, our study highlights unprecedented specificities related to common risk factors that underlie CVD.